Contexts for assessment and outcome evaluation in librarianship - Woodsworth, Anne; Penniman, William David, 1937- (Advances in librarianship,, 2012)
Assessment and outcomes evaluation have become increasingly important in librarianship. Although initially used in educational contexts to measure student learning, the strategy has migrated to other contexts such as hiring, employee development, overall organizational and institutional successes, measuring the outcomes of projects and operational changes, and self assessment at the personal level. This growing emphasis is partly due to increasingly stringent requirements that funds are used effectively to improve services and operations. The current economic climate and retrenchments in non-profit agencies, have raised the need for assessment and outcomes evaluation to a critical level. 'Contexts for Assessment and Outcome Evaluation in Librarianship' focuses not on the how of undertaking assessment and outcomes evaluation, but rather on their successes and failures in various contexts in which these tools have been and will be used.